Electrical Status Epilepticus during Sleep and Evaluating the Electroencephalogram - Drees, Michael; Kulkarni, Neil; Vidaurre, Jorge (Journal of Pediatric Epilepsy, 2021)
Electrical status epilepticus during sleep (ESES) is an age-related, self-limited epileptic encephalopathy characterized by heterogeneous clinical manifestations and a specific electroencephalographic pattern of continuous spikes and waves during slow sleep. The etiology of ESES is not completely clear, although structural brain lesions, abnormal immunological markers, and genetic mutations have been associated with the syndrome. ESES was first described in 1971 and since then, the diagnostic criteria have changed multiple times. Additionally, inconsistency between authors in how to record and evaluate the electroencephalogram also leads to variability between studies. These inconsistencies hamper objectivity, comparison, and generalization. Because of this, one of the first priorities of physicians treating this condition should be defining the parameters of this disease so that cooperative building can occur.
Keywords: electrical status epilepticus during sleep; epileptic encephalopathy; spike-wave index; epileptiform activity